Metabolite profiles and biomarkers of three Selaginella (Selaginellaceae) medicinal plant species in Java Island, Indonesia - AMANDA KHOIRUNISA; TATIK CHIKMAWATI; GIRI NUGROHO; MIFTAHUDIN MIFTAHUDIN (Society for Indonesian Biodiversity, 2025)
Abstract. Khoirunisa A, Chikmawati T, Nugroho G, Miftahudin. 2025. Metabolite profiles and biomarkers of three Selaginella (Selaginellaceae) medicinal plant species in Java Island, Indonesia. Biodiversitas 26: 434-443. Metabolite content in plants is an important taxonomic marker that facilitates the realistic delimitation of species. Substantial improvement is needed for the metabolomic data of several fern species, including Selaginella, which is widely used as a medicinal plant on Java Island. Therefore, this research aimed to profile metabolite compounds in Selaginella ornata, S. plana, and S. willdenowii, and identify biomarkers for species differentiation. Metabolite content and data were determined with Liquid Chromatography-Mass Spectrometry (LC-MS) and MZmine 3.1.0 beta software, respectively. Meanwhile, metabolite profiling, heatmap clusters, and cluster analysis were carried out using MetaboAnalyst 5.0. A total of 113 metabolites were detected in three Selaginella species observed. Based on metabolite characteristics, cluster analysis categorized all individuals into three groups, showing that individuals from the same species were more similar than others, with S. ornata metabolites appearing more similar to S. willdenowii than to S. plana. Three species had similarities in the compounds 1,3,5-benzenetricarbonitrile, 2-hydroxyisocaproic acid, 3-furoic acid, 3-methyl-2-oxovaleric acid, amentoflavone, avobenzone, ibuprofen, kojic acid, and skyrin. Metabolites only possessed by each species of S. plana, S. ornata, and S. willdenowii included 4-vinylphenol, velutin, and axahine B, respectively. This research reported for the first time several low-weight secondary metabolites with potential application as biomarkers to differentiate three species.